RELATION BETWEEN SEED PHYSIOLOGICAL QUALITY OF BLACK OAT AND FORAGE AND SEEDS PRODUCTION - SCHUCH, Luis Osmar Braga; KOLCHINSKI, Eliane Maria; CANTARELLI, Leandro Damero (Scientia Agraria, 2008)
With the objective to evaluate the effect of seed physiological quality on the forage production, regrowth after the cutting and seeds yield of black oats (Avena strigosa Schreb), a field experiment was conducted in the year, in Pelotas, Rio Grande do Sul State, Brazil. This study evaluated five levels of seed physiological quality and two systems management (without cutting/with cutting) of the plants, using black oats common cultivars. Were used the experimental design was a randomized block with three replication. Increases in levels of seed physiological quality provided increments the stems m2, the dry matter production, leaf area index and seed yields. The variation the seed physiological quality did not affect the regrowth capacity of the plants.